Uso de las tecnologías de la información y comunicación y pensamiento crítico en estudiantes del primer grado de secundaria institución educativa Mariscal Oscar Raimundo Benavides, Iquitos 2022 - Perez Ayache, Yesenia (2024)
The study analyzed the connection between the use of ICTs and critical thinking among first-year secondary school students at a public school in Iquitos during 2023. The research used a quantitative method and a relational, cross-sectional design. The sample included 224 students, selected using probability sampling from a sample of 538. Two questionnaire-type instruments were used to collect data. The findings showed that only 9.8% of students achieved a high level in their use of ICTs, while 58.9% were in the medium range and 31.3% were in the low range. Regarding critical thinking, 9.8% achieved a high level, 49.1% a medium range, and 32.1% a low level. Spearman's correlation analysis (p = 0.0000) showed a statistically significant relationship between ICT use and critical thinking, especially in the areas of analysis, inference, argumentation, and solution proposal. These findings suggest that greater ICT use is linked to stronger development of critical thinking.